Light curves and colours of the faint Uranian irregular satellites Sycorax, Prospero, Stephano, Setebos, and Trinculo - Maris, M. (2007)
Context: After the work of Gladman et al. (1998, Nature, 392, 897), it is now assessed that many irregular satellites are orbiting around Uranus. Aims: Despite many studies performed in past years, very little is know about the light-curves of these objects and inconsistencies are present between colours derived by different authors. This situation motivated our effort to improve both the knowledge of colours and light curves. Methods: We present and discuss, the time series observations of Sycorax, Prospero, Stephano, Setebos, and Trinculo, five faint, irregular satellites of Uranus, which were carried out at VLT, ESO Paranal (Chile) on the nights between 29 and 30 July, 2005 and 25 and 30 November, 2005. Results: We derive light curves for Sycorax and Prospero and colours for all of these these bodies. Conclusions: For Sycorax we obtain colours B-V = 0.839 ± 0.014, V-R = 0.531 ± 0.005, and a light-curve which is suggestive of a periodical variation with period ≈3.6 h and amplitude [aprox]0.067 ± 0.004 mag. The periods and colours we derive also for Sycorax are in agreement with our previous determination in 1999 using NTT. We also derive a light-curve for Prospero which suggests an amplitude of about 0.2 mag and a periodicity of about 4 h. However, the sparseness of our data, prevents a more precise characterization of the light-curves, and we can not determine whether they are one-peaked or two-peaked. Hence, these periods and amplitudes have to be considered preliminary estimates. As for Setebos, Stephano, and Trinculo the present data do not allow us to derive any unambiguous periodicity, despite the fact that Setebos displays a significant variability with amplitude about as large as that of Prospero. Colours for Prospero, Setebos, Stephano, and Trinculo are in marginal agreement with the literature.